Penerapan Terapi Akustik Terhadap Peningkatn Kekuatan Otot Ekstremitas Pada Penderita Stroke Melalui Aplikasi Teori Model Betty Neuman Di Rumah Sakit Tiara Sella Kota Bengkulu - Kasih; Rustandi, Handi; Metasari, Des (Utami Publisher, 2025)
Mental health is an emotional stability obtained from one's ability to control oneself by always thinking positively in dealing with environmental stressors without physical,psychological pressure, both internally and externally (Nasir, Abdul., 2011) Nursing theories are attempts to describe or explain nursing phenomena. Through nursing theory, it can be distinguished whether it includes scientific disciplines or other activities. Apart from being used to develop a model related to nursing concepts, nursing theory also has characteristics including: nursing theory identifies and explains special concepts related to real things in nursing. The main concepts identified in Betty Neuman's theoretical approach are the holistic approach, open system (including function, input and output, feedback, negent-copy, and stability), environment (including the created environment), client system (including five client variables, basic structure, line of resistance, normal line of defense, and flexible line of defense), health (fitness to disease), stressors, degree of reaction, prevention as intervention (three levels), and recovery.